Psychological and Social Influences on Organic Food Consumption Behavior in Bangladesh: A Rural–Urban Comparison - Nasrin Lubna (CV. Tripe Konsultan, 2026)
The growing trends of organic food consumptions, worldwide, explore consumer concerns about food safety, health, and sustainability are driving interest of organic food consumptions; however, the consumption behavior of organic food in developing economies are not well understood. This study, thus, aims to explore how psychological and social influences affect behavioral intention for organic food consumption, and how these intentions lead to actual consumption behavior in varied consumer locations (urban vs. rural). Partial Least Squares Structural Equation Modeling (PLS-SEM) was employed for analyzing a survey dataset comprising 204 consumer responses to test the research model which was developed utilizing the Theory of Reasoned Action (TRA). The findings show that both attitudes and subjective norms significantly influence behavioral intentions, with subjective norms having a stronger effect. The behavioral intention also notably impacts actual consumption. While consumer location does not directly affect behavioral intention, it is a crucial moderator in the attitude-intention relationship, highlighting the importance of geographical context. This study enhances the TRA by considering consumer location, offering insights into the factors influencing decision-making. The results suggest that marketers and policymakers should tailor their strategies to geographical distinctions to effectively promote sustainable organic food consumption in Bangladesh.